Neuroprotective effect of acetoxypachydiol against oxidative stress through activation of the Keap1-Nrf2/HO-1 pathway - Yu Qi; Ge Liu; Shengjie Jin; Rong Jian; Ziqiang Zou; Chenjing Wang; Yuanlong Zhang; Min Zhao; Haoru Zhu; Pengcheng Yan (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Excessive oxidative stress in the brain is an important pathological factor in neurological diseases. Acetoxypachydiol (APHD) is a lipophilic germacrane-type diterpene extracted as a major component from different species of brown algae within the genus Dictyota. There have been no previous reports on the pharmacological activity of APHD. The present research aims to explore the potential neuroprotective properties of APHD and its underlying mechanisms. Methods The possible mechanism of APHD was predicted using a combination of molecular docking and network pharmacological analysis. PC12 cells were induced by H2O2 and oxygen–glucose deprivation/reoxygenation (OGD/R), respectively. Western blot, flow cytometry, immunofluorescence staining, and qRT-PCR were used to investigate the antioxidant activity of APHD. The HO-1 inhibitor ZnPP and Nrf2 gene silencing were employed to confirm the influence of APHD on the signaling cascade involving HO-1, Nrf2, and Keap1 in vitro. Results APHD exhibited antioxidant activity in both PC12 cells subjected to H2O2 and OGD/R conditions by downregulating the release of LDH, the concentrations of MDA, and ROS, and upregulating SOD, GSH-Px, and GSH concentrations. APHD could potentially initiate the Keap1-Nrf2/HO-1 signaling cascade, according to the findings from network pharmacology evaluation and molecular docking. Furthermore, APHD was observed to increase Nrf2 and HO-1 expression at both mRNA and protein levels, while downregulating the protein concentrations of Keap1. Both Nrf2 silencing and treatment with ZnPP reversed the neuroprotective effects of APHD. Conclusions APHD activated antioxidant enzymes and downregulated the levels of LDH, MDA, and ROS in two cell models. The neuroprotective effect is presumably reliant on upregulation of the Keap1-Nrf2/HO-1 pathway. Taken together, APHD from brown algae of the genus Dictyota shows potential as a candidate for novel neuroprotective agents.